Institutions, inward foreign direct investment, trade openness and credit level in emerging market economie - Nguyen Phuc Canh; Christophe Schinckus; Thanh Dinh Su; Felicia Chong (Review of Development Finance, 2018)
This study investigates the effects of institutional quality, inward FDI, trade openness, and their interaction on the domestic credit equilibrium in 33 emerging economies between 2002 and 2015. Through two system-GMM estimators, our study shows that inward FDIs have a booming effect on the domestic credit in emerging market economies while the trade openness exhibits a crowding-out effects. Institutions help moderating these effects of inward FDIs and trade openness on the domestic credit suggesting a particular policy.
Keywords: E02; E44; E51; F15; F21; 650; Institutional quality; Inward FDI; Trade openness; Credit equilibrium